Calculation of Technological Consumption (Loss) of Electricity in Modern 0.38–10 kV Electrical Distribution Networks - M. I. Fursanov; A. A. Zalotoy; V. V. Makarevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
. New conditions of functioning of electric power industry, tougher of requirements to technological condition of the industry predetermined transition to restructuring of electric networks on the basis of innovative structure of SMART GRID. This leads to the improvement of traditional tasks of calculation and analysis of modes and technological consumption (loss) of electricity. The authors have developed a promising method of operational calculations of technical losses of electricity in modern electrical networks of 0.38–10 kV on the basis of telemechanical graphs of loads on the head sections of distribution lines, in the area of additional installation of digital metering devices and of sources of distributed generation. The method proposes a new technique for determining the flow of electric energy in the sections of distribution lines. This is done as follows. First, according to the data of additional measurements of the network and taking into account the calculated no-load losses of transformers, electricity flows are calculated in the head sections of 6–10 kV lines. Then, according to the obtained data and the measured values of the active and reactive energy graphs of the head sections, the electric power flows targeted for their subsequent distribution over all sections of the 0.38–10 kV network are determined, taking into account the load losses of electricity and the flow distribution coefficients. The distribution coefficients are the fractions of the calculated phase loads of the 0.38 kV network of their total value. Then, according to the obtained data and the measured values of the active and reactive energy graphs on the head sections, the electric power flows intended for their subsequent distribution over all sections of the 0.38–10 kV network are determined, taking into account the load losses of electricity and the flow distribution coefficients. The basic analytical relations concerning the estimation of losses and mode as well as an example of calculation of technological consumption (loss) of electricity in the general scheme of the distribution network of 0.38; 6 and 10 kV are given. The latter is performed for a single (first)stage of load graphs.